An experimental blade-controlled platform for the design of smart cross-flow propeller. (15th April 2022) - Fasse, Guillaume; Becker, Florent; Hauville, Frederic; Astolfi, Jacques-Andre; Germain, Gregory
Abstract: As an academic platform, the French Naval Academy Research Institute (IRENav) developed a large-scale experimental cycloidal propeller (800 kg, 0.4 m radius) with the aim of running diverse pitch motions to evaluate performances of cross-flow propellers. Blades' pitching is here performed by servo-motors in order to control each blade independently. Blade pitch regulation has been improved to obtain a quick response of auxiliary servo-motors. However, pitch tracking validation shows a systemic error due the PI regulation loop which depends on the rotational speed and the considered pitch law (the sharper the law, the higher the error). The platform is widely instrumented with load and torque sensors to measure inflow hydrodynamic forces during the rotation. First experiments have been performed at the IFREMER wave–current flume tank for a range of sinusoidal pitch laws to confirm the post process procedure and to determine performances for a range of advance parameters. Results show that depending on the advance parameter the more different efficient law is: the higher the advance parameter, the lower the sinusoidal amplitude must be for a better efficiency. These results confirm the requirement of an adaptable pitch control for cycloidal propeller to boost their performances.